Artikel Penelitian / Original Re PERAN ALGORITMA TIKTOK SEBAGAI GATEKEEPER DALAM PEMBENTUKAN AGENDA ISU LINGKUNGAN: Studi Netnografi tentang Kekuasaan Algoritmik, Viralisasi, dan Komunikasi Lingkungan di Ruang Publik Daring - Daffa faisal Daffa; Arif Rahman; Reza Pahlevi; Tanya Chynta (STISIP Widyapuri Mandiri Sukabumi, 2026)
This study explores the role of TikTok’s algorithm as a digital gatekeeping actor in shaping the agenda of environmental issues within the online public sphere. With its massive user base, TikTok functions not merely as an entertainment platform, but as a central arena for meaning production and the circulation of environmental discourse. Employing a qualitative netnographic approach, the research examines how TikTok’s recommendation system prioritizes content based on virality, emotional appeal, and visual attractiveness. The findings reveal that the algorithm amplifies simplified and affective environmental narratives, while marginalizing analytical, structural, and scientifically grounded content. Moreover, personalization mechanisms generate homogeneous information spaces that reinforce filter bubbles and restrict the diversity of perspectives. These results demonstrate that algorithms are not neutral tools, but symbolic forces that actively shape public perceptions of environmental issues. Therefore, adaptive environmental communication strategies are required strategies that engage with algorithmic logic without sacrificing depth, accuracy, and the educational orientation of the message.